Hemodynamic and Autonomic Response to Different Salt Intakes in Normotensive Individuals. Issue 8 (August 2016) - Castiglioni, Paolo; Parati, Gianfranco; Lazzeroni, Davide; Bini, Matteo; Faini, Andrea; Brambilla, Lorenzo; Brambilla, Valerio; Coruzzi, Paolo
Abstract : Background: Even if sodium sensitivity represents a risk factor at any blood pressure (BP) level, limited evidence is available that it may influence cardiovascular control in normotensives, particularly in white individuals. Therefore, the aim of the study was to investigate whether sodium sensitivity alters hemodynamic or autonomic responses to salt in normotensives. Methods and Results: We evaluated the Sodium‐Sensitivity Index (SS‐Index) in 71 white normotensives after 5 days of high‐ and low‐sodium diets. We measured BP continuously at the end of each period, estimating hemodynamic indices from BP waveform analysis, and autonomic indices from heart rate (HR) and BP variability. According to the SS‐Index distribution, we defined 1 sodium‐sensitive group (SS, with SS‐Index >15 mm Hg/[mmol·day]), 1 sodium‐resistant group, (unresponsive to sodium load with −15≤ SS‐Index ≤+15), and 1 inverse sodium‐sensitive group, responsive to sodium by decreasing BP, with SS‐Index <−15). We compared the effects of the diets among groups, and correlated autonomic/hemodynamic indices with the SS‐Index. After sodium loading, a significant decrease in systemic peripheral resistances, HR, spectral indices of BP modulation, and a significant increase of indices of HR vagal modulation were found in the inverse sodium‐sensitive group but not in SS normotensives. Moreover, the highest SS‐Indices were associated with the lesser vagal HR decelerations. Conclusions: Our data suggest that salt sensitivity in white normotensive individuals is associated with impaired vasodilation and altered autonomic response to dietary salt. Such dysfunction may critically contribute to induce a BP response to dietary salt.